Pengaruh Moda Pembelajaran Blended Learning terhdap Peningkatan Hasil Belajar pada Pembuatan Pola Kebaya di SMK Negeri 2 Jombang - Frizkita Putri Amanda; Peppy Mayasari; Imami Arum Tri Rahayu; Deny Arifiana (Journal on Education, 2024)
Blended learning is a learning mode that combines face-to-face (offline) learning and e-learning. Blended learning can be used by teachers to help achieve effectiveness and learning goals. The aim is to find out the implementation of blended learning in making kebaya patterns according to design, find out students' responses to the implementation of the blended learning mode, and find out the effect of blended learning on student learning outcomes. This research is a quasi-experimental or quasi-experimental research with a quantitative approach. Involving research subjects who were class XI Fashion Design 4 students, totaling 32 students, this research used data collection methods is observation, questionnaires and assessment tests. The results of the research show that the application of the blended learning mode in making kebaya patterns in observing teacher and student activities obtained a good category. Student responses using the blended learning mode obtained a very good category. Student learning outcomes using the blended learning mode reach completion in the complete category.